Neutrophil NET Formation with Microbial Stimuli Requires Late Stage NADPH Oxidase Activity - Heather A. Parker (MDPI AG, 2021)
Neutrophils respond to a range of stimuli by releasing extracellular traps (NETs), a mesh consisting of chromatin plus granule and cytoplasmic proteins. We have investigated NET release in response to phorbol myristate acetate (PMA), Pseudomonas aeruginosa (PAO1), Staphylococcus aureus and Candida albicans, and the involvement of NADPH oxidase (NOX2) and myeloperoxidase (MPO) activities. An oxidative mechanism was involved with each stimulus, and the NOX2 inhibitor diphenylene iodonium (DPI) gave almost total inhibition. Notably, DPI added up to 60–90 min after stimulation still gave significant inhibition of subsequent NET formation. As most of the NOX2 activity had already occurred by that time, this indicates a requirement for late-stage low-level oxidant production. Inhibition of histone citrullination did not suppress NET formation, indicating that this was not the essential oxidant-dependent step. With PMA and P. aeruginosa PAO1, MPO activity played an important role in the induction of NETs and MPO inhibitors added up to 30–90 min after stimulation suppressed NET formation. NET formation with S. aureus and C. albicans was insensitive to MPO inhibition. Thus, MPO products are important with some stimuli but not others. Our results extend earlier observations with PMA and show that induction of NETs by microbial stimuli requires late stage oxidant production. Others have shown that NET formation involves NOX2-dependent elastase release from granules. As this is an early event, we conclude from our results that there is more than one oxidant-dependent step.